Profile: Vanessa Cameron – 36 years at the Royal College of Psychiatrists. (December 2016) - Poole, Rob; Robinson, Catherine A.
Abstract : On 16 December 2016, Vanessa Cameron retires as Chief Executive of the Royal College of Psychiatrists. She started working there in September 1980 and in 1984 she became Secretary of the College, the role that preceded chief executive. The College was formed in 1971, so Vanessa has been present for most of its lifetime. It has been a period of continuous change that has seen psychiatry leave the old mental hospitals, expand considerably in the late 1990s and early part of the 21st century, and come under huge pressure more recently. Although she has never worked within mental health services, Vanessa has been at the heart of British psychiatry for 36 years. She was awarded an MBE in the 2013 New Year's Honours list for services to psychiatry.